État de lieux de l’imagerie médicale dans la province de la Tshopo-RDC : besoin de formation des cadres intermédiaires et d’équipement dans un pays à ressources limitées - AHUKA LONGOME Lambert; VALIMUNGIGHE Muhindo Moise; KUYIGWA TOHA Georges; BAMBALE LIMENGO Jean Paul; MUTANDA BASOKANIA Ley; AHUKA ONA LONGOMBE Albert (Journal Africain d Imagerie Médicale (J Afr Imag Méd) Journal Officiel de la Société de Radiologie d’Afrique Noire Francophone (SRANF), 2026)
Background: Medical imaging is a pivotal specialty, essential in the practice of modern medicine. By 2022, most African countries south of the Sahara already have modern medical imaging equipment and qualified medical personnel in this field. This is not the case in the eastern part of the Democratic Republic of Congo in general, and the Province of Tshopo in particular. The objective of this work was to make an inventory of imaging services in the main health facilities of the different health zones of the province of Tshopo. Material and methods: This was a cross-sectional descriptive study conducted between August and November 2022 in the form of a survey of health zone heads and radiology practitioners in the main health institutions. Results: With respect to the distribution of imaging personnel, the results are as follows: 0 radiologists, 2 senior technicians with degrees in radiology, 0 reference personnel in radiation protection and maintenance of radiological installations. In 23 health zones and their main health facilities, 5 X-ray machines and 13 ultrasound machines were recorded. Mammography machines, CT scans and magnetic resonance imaging (MRI) machines were not included in the imaging equipment. Conclusion: In the province of Tshopo, medical imaging reflects shortcomings from every point of view. The provision of diversified imaging equipment and the training of dedicated medical and paramedical staff are imperative to guarantee quality care to the population of the Province of Tshopo.